A meta-analysis of genome-wide association studies revealed significant QTL and candidate genes for loin muscle area in three breeding pigs - Wang Zhenyu; Li Mengyu; Duan Dongdong; Han Jinyi; Qiao Chuanmin; Zhou Hao; Li Xinjian; Zhou Shenping; Xin Wenshui (Scientific Reports)
Abstract Loin muscle area (LMA) is an important production trait in pigs and is highly correlated with lean meat percentage. However, the genetic architecture of LMA has not yet been fully elucidated. This study conducted genome-wide association studies (GWAS) and meta-analyses of LMA in Duroc (n = 337), Landrace (n = 662), and Yorkshire pigs (n = 3,176) using imputed whole-genome sequencing to identify new QTLs and candidate genes associated with LMA traits. A total of 108, 34, and 232 significant variants were identified in the Duroc, Landrace, and Yorkshire populations, respectively. The meta-analysis revealed 143 genome-wide significant SNPs and 276 suggestive SNPs, among which 213 were not identified in single population GWAS. Notably, 229 and 413 SNPs were located on SSC16 in the Yorkshire population and meta-analysis, respectively. Based on the 2-LOD drop-off interval, the SSC16 QTL in the Yorkshire population was further narrowed to a 679.835 kb interval (from 32.818 Mb to 33.498 Mb). The most significant variant within this QTL, 16_33228254 (P = 4.45 × 10–9), explained 1.11% phenotypic variance, representing a potential novel locus for LMA. Further bioinformatics analysis determined seven promising candidate genes (NDUFS4, ARL15, FST, ADAM12, DAB2, PLPP1, and SGMS2) with biological processes such as myoblast fusion and positive regulation of transforming growth factor beta receptor signaling pathway. Among them, ARL15 was previously reported in LMA studies, while the other six genes represent novel candidate genes. These findings reveal potential functional genes and pathways associated with LMA, providing valuable insights for future genetic improvement in pigs.